Leadership in Digital Management at Ar-Risalah Islamic University, Padang - Mohammad Raihan Raihan; Ahmad Rivauzi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
This study analyzes the leadership of the Ar-Risalah Learning Centre (ALC) in managing digital transformation at Ar-Risalah Islamic University, Padang. The study employs a qualitative approach with a single-case study design. Data were collected through semi-structured interviews, moderate participant observation, and document analysis with ALC leadership, teachers, and educational staff. Analysis was conducted through data reduction, data presentation, and the drawing and verification of conclusions. The results of the study indicate that the ALC functions as a middle-management unit that bridges the foundation’s strategic policies and the school’s managerial and pedagogical practices. The ALC exercises leadership through moral-technological exemplarity, the repeated articulation of a digital vision, the stimulation of innovation, individual mentoring, and continuous oversight of digital systems. Digital transformation in schools is not merely the implementation of technology. It is an institutional process that integrates digital competencies, organizational governance, work culture, and Islamic values. This study formulates the Operational Islamic Digital Transformational Leadership (OIDTL) model, a framework for operational-level digital transformational leadership grounded in Islamic values. This model emphasizes that the success of digitalization in Islamic schools is not determined solely by technological infrastructure or top-level leadership policies, but rather depends on operational units that integrate competency development, system oversight, mentoring, and the establishment of a digital work culture. This work culture is grounded in the values of trustworthiness, exemplary conduct, consultation, empathy, and reconciliation. The findings contribute to the study of digital leadership, Islamic educational leadership, and digital transformation management in Integrated Islamic Schools